A Novel Approach by Needles in the Payzone of Heterogeneous Tight Carbonate: A Case Study for Offshore Marginal Field - Li, Rong; Gong, Hao; Al-Shamsi , Mohamed K.; Feng, Peizhen; Lotfy Elbaramawi, Mohamed; Al-Neaimi, Ahmed; Al-Menhali, Helal; Chehabi, Wissam; Abdelhamed, Wael; Loobari, Sultan; Ali, Ahmed Ziad; Obeid, Ahmad Fayyad (International Journal of Petroleum Technology, 2022)
The new Fish-bones Completion & Stimulation approach by needles in the pay stack aims at addressing heterogeneous tight carbonate by increasing flow area in the lower permeable streaks, which is efficient as hundreds of tunnels drain connecting the borewell to the body of the reservoir to increase well productivity and oil recovery. The initial plan includes selecting the best ones from Stair step horizontal well, Dual Lateral well, five lateral fish-bone drilling, and horizontal drilling along with hydraulic fracture. Considering the lessons of failure to clean internal tubes, the modified 4-1/2” Liner is installed in the lower two sub-layer by jetting subs combing with production subs for matrix acidizing in the upper one sub-layer as per modified Fish-bones Completion Design. In addition, special acid-releasing float shoes and new fishing baskets are applied to avoid those previous problems with this well technique. The candidate well shows good oil test and production, which improved by three times at 2000bbl/d with respect to the initial plan in the B field. This paper describes the technology background and characteristics, design factors, modified design, execution, well test, and lessons learned during implementation.